PARTISIPASI MASYARAKAT PADA PROGRAM PEMBANGUNAN BERBASIS LINGKUNGAN - MEMBANGUN PRASARANA LINGKUNGAN DAN SOSIAL (PBL MAPALUS) - Christiviany Gracanti Tatuh; Esry O. H. Laoh; Gene H. M. Kapantow (Sam Ratulangi University, 2017)
This study aims to identify the shape and level of community participation in the planning, implementation, and supervision of Environmental Based Programs - Building Environmental and Social Infrastructure (PBL-Mapalus). The data used in conducting this research are primary data and secondary data. Primary data is data obtained directly in the field, through interviews and observations using questionnaires / questionnaires. Secondary data is data obtained from related institutions such as the Community Empowerment and Manpower Board of Manado City, Office of Lurah Bumi Nyiur and Tuminting Urban Village Office. Sampling technique in this research used Purposive Sampling. This method is done by taking the people who are selected by researchers according to the specific characteristics possessed by the sample. The result of this research can be concluded that community participation in Environment Based Development Program - Building Environmental and Social Infrastructure (PBL-Mapalus) shows the activity of society is big enough. Although there are still a handful of people who do not know about Environmental-Based Development - Building Environmental and Social Infrastructure (PBL-Mapalus) so it is advisable to the relevant agencies to provide more socialization to the community.